2010
DOI: 10.1007/s10973-010-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermal analysis in nanotechnology

Abstract: The analysis of purification and carbonization process in argon with use of nc-TiC x /C powder, obtained by sol-gel method, is presented. TG-DSC measurements were carried out under non-isothermal and isothermal conditions. The samples were heated up in series to 1473, 1573, 1673, and 1773 K. For this series description of process kinetics is presented. Four stages of the process have been distinguished. Kinetics was described using Coats-Redfern equation. The kinetic parameters were determined for particular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As matrix materials commercially pure Ti powders from SLM Solutions GmbH, and as the hard, second-phase nc-TiC particles, in powder form were used. The nc-TiC powders were obtained by non-hydrolytic sol-gel methods [8]. The average size of TiC crystallites was 40 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As matrix materials commercially pure Ti powders from SLM Solutions GmbH, and as the hard, second-phase nc-TiC particles, in powder form were used. The nc-TiC powders were obtained by non-hydrolytic sol-gel methods [8]. The average size of TiC crystallites was 40 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The method synthesis, structure and morphology of nc-TiC powder were presented earlier [8]. The size of crystallites, morphology phase and chemical composition of the composites were determined with the following techniques: X-Ray diffraction (XRD) using PANalytical PW3040/60 X'Pert Pro with Cu Kα radiation, scanning electron microscopy (SEM) using HITACHI SU apparatus equipped with THERMO FISHER NORAN 7 microanalysis adapter.…”
Section: Methodsmentioning
confidence: 99%
“…[ 65 ]. In combination with DSC or other techniques such as infrared spectroscopy, mass spectrometry, or gas chromatography-mass spectrometry a comprehensive evaluation of the thermal characteristic of nanomaterials is possible [ 66 ].…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…The n=6 kinetic model was observed to be the best fitted for all the system during kinetic model determination by applying Coats-Refern method. Biedunkiewicz et al (2010) performed TG-DSC measurements under non-isothermal and isothermal conditions at four different temperatures and used Coats-Redfern method to describe the kinetic parameters. Maitra et al (2008) synthesized zeolite gel and showed that gel dehydration followed first order kinetics and it proceeded through low energy diffusion controlled process.…”
Section: Introductionmentioning
confidence: 99%